The Impact of the Postwar Compromise on Canadian Unionism: The Formation of an Auto Worker Local in the 1950s - Wells, Don (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1995)
At the heart of Canada's "Fordist" class compromise after World War II lay a new unionism which reinforced managerial control in the workplace. By repudiating rank-and-file initiatives against various dimensions of management control of the labour process, the new unionism displaced a potentially transformative kind of unionism that arose during the war. The significance of this transition is explored through a comparative examination of the relations between union leaders and members at two autoworker locals, one of which exemplified the ran-and-file-oriented local unionism of the war years, the other the new centralized unionism which came in its wake. It is argued that this transition to a new unionism was a key contributor to the marginalisation of class-based politics in Canada after the war.